Association between SARS-CoV-2 Infection and Adverse Perinatal Outcomes in a Large Health Maintenance Organization - Getahun, Darios; Peltier, Morgan R.; Lurvey, Lawrence D.; Shi, Jiaxiao M.; Braun, David; Sacks, David A.; Burgos, Anthony E.; Fong, Alex; Trivedi, Neha; Yasumura, Lyn; Reynolds, Kristi; Nguyen, Marielle; Volodarskiy, Marianna; Chiu, Vicki Y.; Lopez, Adrian H.; Fassett, Michael J. (American Journal of Perinatology, 2022)
Objective This study aimed to examine whether severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection during pregnancy is associated with increased odds of perinatal complications and viral transmission to the infant.Study Design A retrospective cohort study of women who delivered at Kaiser Permanente Southern California hospitals (April 6, 2020–February 28, 2021) was performed using data extracted from electronic health records (EHRs). During this time polymerize chain reaction (PCR)-based tests for SARS-CoV-2 was universally offered to all pregnant women at labor and delivery admission, as well as earlier in the pregnancy, if they were displaying symptoms consistent with SARS-CoV-2 infection or a possible exposure to the virus. Adjusted odds ratio (aOR) was used to estimate the strength of associations between positive test results and adverse perinatal outcomes.Results Of 35,123 women with a singleton pregnancy, 2,203 (6%) tested positive for SARS-CoV-2 infection with 596 (27%) testing positive during the first or second trimester and 1,607 (73%) during the third trimester. Women testing positive were younger than those who tested negative (29.7 [5.4] vs. 31.1 [5.3] years; mean [standard deviation (SD)]; p < .001). The SARS-CoV-2 infection tended to increase the odds of an abnormal fetal heart rate pattern (aOR: 1.10; 95% confidence interval [CI]: 1.00, 1.21; p = 0.058), spontaneous preterm birth (aOR: 1.28; 95% CI: 1.03, 1.58; p = 0.024), congenital anomalies (aOR: 1.69; 95% CI: 1.15, 2.50; p = 0.008), and maternal intensive care unit admission at delivery (aOR: 7.44; 95% CI: 4.06, 13.62; p < 0.001) but not preeclampsia/eclampsia (aOR: 1.14; 95% CI: 0.98, 1.33; p = 0.080). Eighteen (0.8%) neonates of mothers who tested positive also had a positive SARS-CoV-2 test after 24 hours of birth, but all were asymptomatic during the neonatal period.Conclusion These findings suggest that prenatal SARS-CoV-2 infection increases the odds of some adverse perinatal outcomes. The likelihood of vertical transmission from the mother to the fetus was low (0.3%), suggesting that pregnancy complications resulting from SARS-CoV-2 infection pose more risk to the baby than transplacental viral transmission.Key Points
Keywords: COVID-19; SARS-CoV-2; infection; pregnancy; outcomes; pandemic